Hospital staff’s attitudes toward and knowledge about dementia before and after a two-day dementia training program - Schneider, Julia; Schönstein, Anton; Teschauer, Winfried; Kruse, Andreas; Teichmann, Birgit (Journal of Alzheimer's disease, 2020)
Background: The outcomes of hospitalized People with Dementia (PwD) are likely to be negative due to, among other key causes, negative staff attitudes and limited staff knowledge regarding dementia. Targeted interventions have been shown to positively change the attitudes of the hospital staff while also increasing their overall knowledge of dementia. However, training effects are often short-lived and frequently long-term effects are not examined in studies. Objective: To examine whether attending a dementia training program changes the attitudes of hospital staff toward PwD and/or increases their knowledge levels about dementia, and whether or not these changes are stable. Methods: The training program lasted two days and N=60 attending hospital staff members agreed to participate in the study. Data were assessed with questionnaires prior to the training, 3 months, and 6 months after the training. German versions of the Dementia Attitude Scale (DAS-D) and the Knowledge in Dementia (KIDE) scale were used. Additionally, data about perception of PwD and confidence in dealing with challenging behavior were collected and analyzed. Results: After the training program, participants showed a significantly better attitude toward PwD as measured by DAS-D. These time-effects occurred in both DAS-D subscales (“dementia knowledge” and “social comfort”). Although a positive trend could be seen in the KIDE scale, no statistically significant increase occurred over time. Conclusion: Specialist training programs seem to be promising in positively changing attitudes toward and increasing knowledge about PwD with long-term effects. Further research should address the effects of attitude change in patient care.
Gesehen am 25.11.2020